Herpes zoster following intra-articular corticosteroid injection - Fernandes, Neil F. (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2009)
Localized herpes zoster following intra-articular corticosteroid injection is remarkable. We describe an 80-year-old woman with severe osteoarthritis that received an intra-articular injection of 80 mg methylprednisolone in her knee,followed 1 day later by the appearance of linear unilateral vesicles and bullae on her leg in a dermatomal distribution adjacent to the injection site.The roofs of several blisters showed classic viral cytopathic effects forherpes including keratinocytes with multinucleation and margination of chromatin. Varicella zoster virus immunostaining revealed positive staining inthe keratinocytes. One plausible explanation is herpes zoster virus reactivation secondary to localized immunosuppression from corticosteroid injection.
Keywords: Administration & Dosage; Adverse Effects; Aged, 80 And Over; Etiology; Glucocorticoids; Glukokortikoidi; Herpes Zoster; Injections, Intra-Articular; Injekcije intraartikularne; Methylprednisolone; Metilprednizolon; Pathology; Starost 80 in več; Virus Activation; Virusna aktivacija